Pemetaan Inovatif Variasi Dalam Dialek Batak Toba di Kabupaten Aceh Tenggara - Best, Chiristi; Khalsiah, Khalsiah; Mahsa, Masithah (Jurnal Ilmiah Kanderang Tingang, 2025)
This study discusses the variation in vocabulary and pronunciation in the Toba Batak dialect and the causes of the variation in the Toba Batak dialect in Southeast Aceh Regency. The results of the researcher in this study aim to describe the differences in vocabulary and pronunciation used by Toba Batak speakers in the area, then map the variation based on region. The approach used in this study is qualitative. Data collection uses the ability to engage and interview techniques. The data of this study is oral data in the form of Toba Batak dialect words. The source of data in this study is a Toba Batak speaker who lives in Southeast Aceh, the researcher chose 2 sub-districts as the location of the study because it is considered to represent the variety of dialects in Southeast Aceh Regency. The results of the data analysis found that there were differences in vocabulary and pronunciation but the meaning was the same and there was the same pronunciation but different meanings and there was the same vocabulary but had different meanings in the Toba Batak dialect. This difference is influenced by several factors such as geographical factors, social factors, situational factors, and cultural factors in the area. Keywords: language variation, Toba Batak Dialect, vocabulary, pronunciation